'My Brain Made Me Do It?' Reflections on the Role of Neuroscience in Assessing Criminal Responsibility – A South African Medico-legal Perspective. Issue 2 (3rd March 2020) - Stevens, Geert Philip
Abstract : Recently the role of neuroscience in assessing criminal responsibility has become an issue of academic and practical debate. The question that arises is the role that neurological or brain disorders can play in assessing criminal responsibility. Within the context of South African criminal law, the question arises as to whether these disorders will meet the threshold requirements for the defence of pathological criminal incapacity. Various medico-legal issues arise when assessing the role of neurological disorders in relation to criminal responsibility. In this contribution, the reflections are provided pertaining to the role of neuroscientific evidence in explaining criminal responsibility within the context of selected areas of application. Evidentiary aspects pertaining to the presentation of neuroscientific evidence are further canvassed as well as the role of neuroscientific evidence advanced in support of mitigation of punishment.